Adverse Events Following Immunization: Management Preparedness Among Health Workers of Sunsari, Nepal - Katuwal, Suprabha; Shah, Tara; Badhu, Angur; Lamsal, Shyam; Sigdel, Rambha (Journal of Biratnagar Nursing Campus, 2025)
Introduction: An Adverse Event Following Immunization (AEFI) refers to any unwanted medical condition that occurs after vaccination, whether or not it is caused by the vaccine. Maintaining and strengthening public confidence in the national immunization program requires health personnel to be aware of AEFI and adequately prepared to respond to public concerns. The objective of this study was to assess the management preparedness on AEFI among health workers of Sunsari, Nepal.Methods: A descriptive cross-sectional study was carried out between March 2019 and March 2020 among 96 health workers selected by simple random sampling. Information was collected through interviews using a semi-structured questionnaire to assess knowledge and factors associated with AEFI management preparedness. Knowledge levels were classified as poor, fair, and good. Preparedness factors were analyzed descriptively and categorized as always, sometimes, and never, and supported by observation of the AEFI kit box. Mann–Whitney U and Kruskal–Wallis H tests were used to determine the association between socio-demographic variables and knowledge scores.Results:  Findings showed that 63% of the respondents had fair knowledge, 28% had good knowledge, and 9% of the respondents had poor knowledge of AEFI. All of the visited organisations had failed to make available the AEFI Kitbox for their routine immunization program.Conclusion: The study concluded that health workers had proper management preparedness in Sunsari, Nepal. The knowledge regarding AEFI was found fair among them and the majority had followed the guidelines to conduct immunization program, but there was a failure of availability of the AEFI management Kitbox, including articles for the regular immunization program for immediate management if an adverse effect occurs. No significant association was found between socio-demographic characteristics and knowledge regarding AEFI (p>0.05).